Updated use of TACE for hepatocellular carcinoma treatment: How and when to use it based on clinical evidence. (January 2019) - Raoul, Jean-Luc; Forner, Alejandro; Bolondi, Luigi; Cheung, Tan To; Kloeckner, Roman; de Baere, Thierry
Highlights: TACE is the standard-of-care for the treatment of intermediate stage HCC. DEB-TACE is not superior to conventional TACE in efficacy and safety. Several studies demonstrated the clinical benefit to combine cTACE and RFA. Outside stage B, TACE can treat lesions/patients not eligible to other treatments. Further studies are required to state the place of TACE outside intermediate stage. Abstract: Hepatocellular carcinoma (HCC) is the most common primary liver cancer, representing the sixth leading cause of cancer and the third leading cause of cancer-related mortality. Patient stratification and treatment allocation are based on tumor stage, liver function, and performance status. According to the Barcelona Clinic Liver Cancer (BCLC) staging system, transarterial chemoembolization (TACE) is the first-line treatment for patients with intermediate stage HCC, including those with large or multinodular HCC, well-preserved liver function, and no cancer-related symptoms or evidence of vascular invasion or extrahepatic spread. Two TACE techniques have been used since 2004, conventional TACE (cTACE) and TACE with drug-eluting beads (DEB-TACE). cTACE was evidenced first to treat intermediate stage HCC patients. It combines the transcatheter delivery of chemotherapy using Lipiodol-based emulsion plus an embolizing agent to achieve strong cytotoxic and ischemic effects. Drug-eluting beads (DEBs) were developed in order to slowly release chemotherapeutic agents, and to increase ischemia intensity and duration. Recent advances allow TACE treatment of both early stage patients (i.e. those with a solitary nodule or up to 3 nodules under 3 cm) and some advanced stage patients. Here we review recent clinical evidence related to TACE treatment of patients with early, intermediate, and advanced stage HCC. Based on the 2014 TACE algorithm of Raoul et al., this international expert panel proposes an updated TACE algorithm and provides insights into TACE use for patients at any HCC stage.